On the solving of Poisson’s equation for a cylindrical interaction region - Грицунов, А.В.; Бондаренко, И.Н.; Карнаушенко, В.П.; Пятайкина, М.И.; Сова, А.В. (Radiotekhnika, 2019)
A new numerical method for fast solving of Poisson’s equation in the simply connected interaction regions of O-type vacuum microwave devices is described. The principal specificity of this method, so-called Fourier analysis and eigenfunction decomposition (FAED), consists in using the finite Fourier series for the approximation of the radial dependence of electrostatic potential instead of the well-known Hockney’s cyclic reduction (CR) algorithm. This allows using Neumann boundary condition for the electrostatic potential at the axis of the interaction region instead of Dirichlet one, as in M-type devices.